The Relations Among Childhood Maltreatment and Later Intimate Partner Violence Victimization With and Without a Weapon in a Sample of Pregnant Black Individuals - Huibregtse, Megan E. (Journal of interpersonal violence, 2025)
Black pregnant and postpartum individuals are at risk for intimate partner violence (IPV), and those with a history of childhood maltreatment and IPV are even more likely to be re-victimized during pregnancy. However, it is unknown if specific types of child maltreatment predict later IPV with and without a weapon better than others. The current study sought to (i) document the prevalence of childhood maltreatment and IPV and (ii) examine the relations among types of childhood maltreatment and later IPV with and without a weapon within a sample of Black individuals seeking prenatal care at a large public hospital in the southeastern United States. Participants (n = 186; mean age = 27.2 years, SD = 5.3) completed measures assessing childhood maltreatment and IPV with and without a weapon. Approximately 68.5% of participants (n = 124) endorsed experiencing childhood maltreatment, while 42.6% (n = 78) endorsed experiencing IPV. The bivariate relations among five childhood maltreatment types (i.e., sexual, physical, and emotional abuse, physical and emotional neglect) and IPV with and without a weapon were assessed. All childhood maltreatment subtype scores—except childhood physical neglect—were significantly higher among participants who reported a history of IPV with or without a weapon compared to participants who denied a history of IPV with or without a weapon. Logistic regression models revealed childhood sexual abuse emerged as the only significant predictor of experiencing IPV with a weapon (B = 0.10, p = .003) and IPV without a weapon (B = 0.11, p = .001). For every point increase in childhood sexual abuse subtype score, the odds of experiencing IPV with and without a weapon increased by 10% (OR = 1.10, 95%CI [1.04, 1.18]) and 12% (OR = 1.12, [1.05, 1.20]), respectively. Findings suggest that screening for childhood sexual abuse may provide a critical opportunity for maternity care providers to identify individuals at increased risk for IPV victimization with and without a weapon.